Optimization Strategies for Purification of Mycophenolic Acid Produced by Penicillium brevicompactum - Anand S.; Srivastava P. (My University, 2025)
The microbial fermentation of Penicillium brevicompactum produces secondary metabolite mycophenolic acid (MPA), which exhibits antifungal, antiviral, antibacterial, and antitumor activity. It is also a potent, selective, non-competitive, and reversible inhibitor of the human inosine monophosphate dehydrogenase (IMPDH). This study is an attempt to optimize the MPA production through a fermentation process using Penicillium brevicompactum and its further purification process optimization. In the batch fermentation process, the maximum concentration of MPA (1.84 g/L) was attained in a 3.7 L stirred tank reactor. Response surface methodology (RSM) using central composite design (CCD) was employed as a statistical tool to investigate the effect of pH, the volume of eluent and flow rate of the mobile phase on MPA purification process. Under optimum conditions, the experimental yield was observed to be 84.12%, which matched well with the predictive yield of 84.42%. High-performance liquid chromatography (HPLC) and Fourier-transform infrared spectroscopy (FTIR) analysis of the fermented product was carried out to confirm the presence of mycophenolic acid. The MPA purification was done by using column chromatography technique. The purification of broth involved mycophenolic acid extraction by selecting different solvents on the basis of polarity and the extraction efficiency of solvent. Various solid support materials were used for MPA purification in column chromatography. The MPA recovery through alumina column was observed to be 84.12% under the optimum conditions, which was maximum elution as compared with other support materials. The optimized purification process yielded pure MPA crystals. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.